Influence of heavy rainfall on airplane aerodynemic characteristics - Лазнюк, П. С.; Жданов, А. И.; Виноградский, П. М. (Proceedings of National Aviation University (archive), 2000)
Carried out is experimental research of aerodynamic characteristics of airplane model in condition of simulated heavy rainfall in wind tunnel ТАД-2 KIUCA (Kyiv International University of Civil Aviation)